IbM PENERAPAN BIOTEKNOLOGI DAN PENGOLAHAN LIMBAH MEDIA TANAM JAMUR MERANG DI KECAMATAN NISAM KABUPATEN ACEH UTARA - Zuriani zuriani; Rosnina Rosnina; Martina Martina (Universitas Bengkulu, 2018)
The cultivation of mushroom in Nisam Subdistrict is constrained by several factors, such as the limited ability of biotechnology breeding and cultivation, marketing and capital. After harvesting, planting media left without any further processing. Moreover, partner farmers has obstacles in terms of marketing and capital limitations for business development. Mushroom cultivation activity was doing by a farmer group